2007
DOI: 10.1002/crq.177
|View full text |Cite
|
Sign up to set email alerts
|

Conflict within the structure of peer mediation: An examination of controlled confrontations in an at‐risk school

Abstract: The purpose of the research reported in this article was to examine the conflict mediation process among middle school students through critical observations and by addressing the disputants' perceptions of their experiences. The interactions and mediations that were observed are examined by the ways in which mediators' adherence to, and deviation from, the mediation script influenced the mediation and the disputants' perceptions of their mediation experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…Analysis of adult-children interactions confirms the conclusion that Nix and Hale (2007) reached for peer mediation: unexpected reactions to mediators' actions can project their normative and cognitive expectations, which turn out to be ineffective. Furthermore, the analysis confirms that attempts to dictate to children how to resolve conflicts and maintain control of the interaction prevent children from becoming active parties in the process of conflict management (Jenkins, Ritblatt, and McDonald, 2008).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Analysis of adult-children interactions confirms the conclusion that Nix and Hale (2007) reached for peer mediation: unexpected reactions to mediators' actions can project their normative and cognitive expectations, which turn out to be ineffective. Furthermore, the analysis confirms that attempts to dictate to children how to resolve conflicts and maintain control of the interaction prevent children from becoming active parties in the process of conflict management (Jenkins, Ritblatt, and McDonald, 2008).…”
Section: Discussionsupporting
confidence: 55%
“…This analysis helps to understand the differences between forms of communication that can shape CRE. It confirms that the success of CRE depends on its implementation, that is, on the specific form of communication involving mediators and disputants (Nix and Hale, 2007). Some research has demonstrated that CRE is more successful with adolescents than with younger children, presuming that the reason for this lies in the higher degree of cognitive abilities among the former (Garrard and Lipsey, 2007).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…El concepto de convivencia escolar va tomando fuerza progresivamente y evolucionando hasta convertirse en un objetivo central del proceso educativo (García-Raga & López, 2014). En este contexto, la mediación se nos presenta como una estrategia que permite su mejora, junto con otras potencialidades educativas señaladas en una diversidad de estudios, tanto empíricos (Cowie & Wallace, 2000;García-Longoria, 2002;Grande, 2010;Ibarrola-García & Iriarte, 2014;Moral & Pérez, 2010;Nix & Hale, 2007;Paulero, 2011;Torrego & Galán, 2008;Turnuklu et. al., 2010;Villanueva, Usó & Adrián, 2003;) como teóricos (Bonafe-Schmitt, 2000;Boqué, 2003;García-Raga, Martínez-Usarralde & Sahuquillo, 2012;López, 2007;Pulido, Martínez-Seoane & Lucas-Molina, 2013).…”
Section: Antecedentes Y Fundamentación Teóricaunclassified